Cardiorespiratory responses to hypoxia in the African catfish, Clarias gariepinus (Burchell 1822), an air-breathing fish - Belao, T. C.; Leite, C. A. C. [UNESP]; Florindo, L. H. [UNESP]; Kalinin, A. L.; Rantin, F. T. (Springer Heidelberg, 2011)
The African catfish, Clarias gariepinus, possesses a pair of suprabranchial chambers located in the dorsal-posterior part of the branchial cavity having extensions from the upper parts of the second and fourth gill arches, forming the arborescent organs. This structure is an air-breathing organ (ABO) and allows aerial breathing (AB). We evaluated its cardiorespiratory responses to aquatic hypoxia. To determine the mode of air-breathing (obligate or accessory), fish had the respiratory frequency (f(R)) monitored and were subjected to normoxic water (PwO(2) = 140 mmHg) without becoming hyperactive for 30 h. During this period, all fish survived without displaying evidences of hyperactivity and maintained unchanged f(R), confirming that this species is a facultative air-breather. Its aquatic O(2) uptake ((V) over dot O(2)) was maintained constant down to a critical PO(2) (PcO(2)) of 60 mmHg, below which (V) over dot O(2) declined linearly with further reductions of inspired O(2) tension (PiO(2)). Just above the PcO(2) the ventilatory tidal volume (V(T)) increased significantly along with gill ventilation ((V) over dot G), while fR changed little. Consequently, the water convection requirement (V) over dot G/(V) over dot O(2)) increased steeply. This threshold applied to a cardiac response that included reflex bradycardia. AB was initiated at PiO(2) = 140 mmHg (normoxia) and air-breathing episodes increased linearly with more severe hypoxia, being significantly higher at PiO(2) tensions below the PcO(2). Air-breathing episodes were accompanied by bradycardia pre air-breath, to tachycardia post air-breath.
Keywords: Hypoxia; Oxygen uptake; Gill ventilation; Critical oxygen tension; Heart rate; Air-breathing